Production of acetone, butanol, and ethanol by electro-fermentation with Clostridium saccharoperbutylacetonicum N1-4 (2023)
This manuscript describes the effect of altering the extracellular redox potential during the production of acetone, butanol, and ethanol on a dual chamber H-type microbial fuel cell by fermenting glucose with Clostridium saccharoperbutylacetonicum N1-4. Extracellular redox potential modification was achieved by either supplementing the microbial broth with the redox agent NADH or by poising the cathode potential at − 600 mV vs. Ag/AgCl. The addition of NADH was found to foment the production of acetone via fermentation of glucose. The addition of 200 mM of NADH to the catholyte rendered the highest production of acetone (2.4 g L-1), thus outperforming the production of acetone by conventional fermentation means (control treatment) by a factor of 2.2. The experimental evidence gathered here, indicates that cathodic electro-fermentation of glucose favors the production of butanol. When poising the cathode potential at − 600 mV vs Ag/AgCl (electro-fermentation), the largest production of butanol was achieved (5.8 g L-1), outperforming the control treatment by a factor of 1.5. The production of ABE solvents and the electrochemical measurements demonstrate the electroactive properties of C. saccharoperbutylacetonicum N1-4 and illustrates the usefulness of bio-electrochemical systems to improve conventional fermentative processes.